Therapeutic Potential of Hydrogen-Rich Water on Muscle Atrophy Caused by Immobilization in a Mouse Model - Seyedeh Elnaz Nazari; Alex Tarnava; Nima Khalili-Tanha; Mahdieh Darroudi; Ghazaleh Khalili-Tanha; Amir Avan; Majid Khazaei; Tyler W. LeBaron (MDPI AG, 2023)
Skeletal muscle atrophy is associated with poor quality of life and disability. Thus, finding a new strategy for the prevention and treatment of skeletal muscle atrophy is very crucial. This study aimed to investigate the therapeutic potential of hydrogen-rich water (HRW) on muscle atrophy in a unilateral hind limb immobilization model. Thirty-six male Balb/C mice were divided into control (without immobilization), atrophy, and atrophy + hydrogen-rich water (HRW). Unilateral hind limb immobilization was induced using a splint for 7 days (atrophy) and removed for 10 days (recovery). At the end of each phase, gastrocnemius and soleus muscle weight, limb grip strength, skeletal muscle histopathology, muscle fiber size, cross-section area (CSA), serum troponin I and skeletal muscle IL-6, TNF-α and Malondialdehyde (MDA), and mRNA expression of NF-κB, BAX and Beclin-1 were evaluated. Muscle weight and limb grip strength in the H2-treated group were significantly improved during the atrophy phase, and this improvement continued during the recovery period. Treatment by HRW increased CSA and muscle fiber size and reduced muscle fibrosis, serum troponin I, IL-6, TNF-α and MDA which was more prominent in the atrophy phase. These data suggest that HRW could improve muscle atrophy in an immobilized condition and could be considered a new strategy during rehabilitation.